An interview with Božidar Manić about temples - Stanimirović, Mirko (Arhitektura i urbanizam, 2020)
This paper presents an interview with architect Božidar Manić. The topics of conversation are: the rules for building Serbian Orthodox churches in the 21th century, the relationship between tradition and traditionalism within Orthodox architecture, the influence of the liturgy on the shape of a church, the symbolism of the dome, the development of Serbian sacral architecture, and recommendations for designing modern churches. The talks within the project “Temples about temples” are designed to overcome the current crisis of criteria for building Serbian Orthodox churches, through the cooperation of all participants in the construction of a temple. Through conversations with contemporary architects, the author tries to advance the future creation of ambiences, cities and shrines. The most important conclusions of the conversation with Božidar Manić are: tradition and traditionalism are not the same, there are no binding rules related to the architectural form of a church, the temple space should enable worship without interruptions and the altar must be on the east, separated from the nave.
Keywords: Božidar Manić; architecture; Orthodox church; interview